EFFECTS OF CONSCIOUS CONNECTED BREATHING EXERCISES ON BURNOUT LEVELS, SELF-ESTEEM, AND SELF-COMPASSION AMONG FEMALE HEALTHCARE WORKERS - Gulsum Uysal; Gulhan Yuksel; Merthan Tunay; Azize Yilmaz Gumus (Eskisehir Medical Journal, Eskisehir City Hospital, 2026)
Introduction: Burnout is a public health issue due to its effects on patients and public funds. We aimed to determine the impact of breathing sessions on the levels of burnout, self-esteem, and self-compassion among healthcare workers. Methods: A total of 52 participants were enrolled. The Brief Resilience Scale (BRS), Maslach Burnout Inventory (MBI), Rosenberg Self-Esteem Scale (RSES), and Self-Compassion Scale (SCS) questionnaires were completed prior and after the breathing group sessions. The scores were analyzed for comparison. Results: The average age and duration of employment of the group was 42.48 ± 7.9 and 20.03 ± 9.37 years; respectively. Concerning MBI ratings, emotional exhaustion greatly diminished, but personal accomplishment significantly rose following breathing sessions (p = 0.001). The average score of the RSES was 30.82 prior to the breathing sessions and 33.07 subsequent to them and significant elevation in self-esteem score was noted following the CCB sessions (p= 0.001). All SCS scores, apart from shared humanity and isolation, exhibited statistically significant differences before and after the breathing sessions (p